Clinical Profile of posterior segment in high Myopia - Kaiti, Raju; Bogati, Birkha; Shyangbo, Ranjila; Khadka, Simanta; Bajgai, Priya (Journal of Nepal Health Research Council, 2024)
Background: Myopia is a growing global health concern, with prevalence surging, especially in East and Southeast Asia. The World Health Organization identifies high myopia as -5.00 diopter or less, carrying an elevated risk of irreversible blindness. In 2020, an estimated 2.6 billion people had myopia, projected to reach 4.7 billion by 2050, leading to a rise in complications like myopic maculopathy. This study, conducted in Nepal, where 47.16% of the population is myopic, aims to assess fundus and optic nerve changes in high myopia, examining associations with age, gender, axial length, and mean spherical error. Methods: A prospective, cross sectional study was conducted by recruiting 98 high myopic eyes (defined as spherical equivalent of <-5.0 diopters (D) or axial length â‰¥ 26.00 mm). Colored Fundus photography was performed on viewing angle of 500 in different field of gazes following pupillary dilatation. Fundus photographs were graded by independent graders to evaluate for high myopic fundus and optic disc changes. Multinomial logistic regression was performed with axial length and mean spherical error as risk and myopic changes as dependent variable. Results: In this study, tessellated fundus (57.1%) and peripapillary atrophy (40.8%) were the most common posterior segment changes in high myopic Nepalese subjects. High myopic features were seen in 45.9% of cases. Increase in axial length and mean spherical error was established as a risk factor for development of high myopic changes in the fundus. Conclusions: In this study of the highly myopic Nepalese population visiting tertiary eye hospital, myopic changes such as tessellated fundus and peripapillary atrophy were frequent and were associated with axial length and mean spherical error. Keywords: Degenerative myopia; high myopia; pathologic myopia; peripapillary atrophy; tessellated fundus.